Pengaruh model problem based learning (PBL) terhadap kemampuan koneksi matematis siswa kelas X SMK Negeri Pertanian Terpadu Provinsi Riau - Anggraini, Yola Putri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the mathematical connection ability of the tenth grade students of the Integrated Agriculture State Vocational School of Riau Province in 2018/2019. The form of this research is quasi-experiment and Nonequivalent Control Group Design research design with the sampling technique used is purposive sampling. The population of this study was the whole class X of the Integrated Agriculture State Vocational School in Riau Province Academic Year 2018/2019. The research samples were taken two classes is the experimental class using the Problem Based Learning (PBL) model and the control class using conventional learning. The data collection instruments in this study were implementation sheets, pretest and posttest sheets. Data collection techniques were done by test techniques. Data analysis techniques are descriptive analysis and inferential analysis. Based on the Mann-Whitney U Test for data not normally distributed this study obtained the results that there was an effect of the Problem Based Learning (PBL) model on students’ mathematical connection abilities. So that the learning process carried out using the Problem Based Learning (PBL) model in the research has improved.